Chemical Castration as an Evolving Concept: Is It a Possible Solution for Sexual Offences? - Çöpür, Mazlum (The journal of forensic psychiatry & psychology, 2021)
As growing criminal offences, sexual offences defined by any sexual behavior lacking clear consent, creates significant morbidity, psychiatric comorbidities, adjustment disorders and mortality worldwide. Criminal laws vary between countries while use of chemical castration methods such as hormonal therapies or surgical castration techniques has been implemented in multiple states and countries while number of countries implemented castration methods have increased rapidly in recent years. Despite such trend no comprehensive randomized controlled trial or meta-analysis study has been performed yet. Additionally, multiple ethical questions arise regarding such castration techniques in sexual offenders. In this study our aim is to demonstrate efficiency and possible adverse effects of hormonal and surgical castration techniques, variations among countries and states, and ethical issues.